(untitled) (Global Journal of Science Frontier Research, 2016)
Previous time-symmetric but non-relativistic interpretation of the single-electron doubleslit experiment, visualizing the particle-wave dual nature of the electron, is extended to a relativistic interpretation of the singular nature of the electron as a quantum anomaly occurring at Compton scale distances (ultraviolet regions) from the point particle source and the detection point, violating time-symmetry and local causality. The lensing action of the double-slit is next compared to the lensing action of galaxy cluster or black hole in the foreground of a distant extragalactic light source and extended to a semi-closed Friedman model of the recently observed binary back hole emitting a trangent gravitational wave signal. Historical comments are given on the early philosophical notion of the reality of the intermediate states between source and detector.